An observational study on surgical site infections in the tertiary care centre of Jharkhand. - Prasad, Amit Vikram; Baskey, Shyam Charan; Bhasker, Vivek (Student’s Journal of Health Research Africa, 2024)
Background Surgical site infections (SSIs) are one of the most common postoperative complications and a major contributor to increased morbidity, prolonged hospital stays, and healthcare costs, particularly in resource-constrained settings. Despite the implementation of preventive measures, SSIs remain prevalent in many Indian healthcare institutions, especially in tertiary care centres with high patient loads. Aim: To determine the incidence, risk factors, microbial profile, and clinical outcomes associated with surgical site infections in patients undergoing surgery at a tertiary care centre in Jharkhand. Methods This prospective observational study included 100 patients undergoing various surgical procedures in the Department of Surgery at a tertiary care hospital in Jharkhand. Patients were followed for 30 days postoperatively for signs of SSIs. Data on demographics, comorbidities, surgical characteristics, and microbiological findings were collected. Statistical analysis was performed using SPSS version 23.0, with significance set at p < 0.05. Results Out of 100 participants, 18 (18%) developed SSIs. Superficial incisional infections were the most common (11%), followed by deep incisional (5%) and organ/space infections (2%). Significant risk factors associated with SSIs included diabetes mellitus (p = 0.002), surgery duration >2 hours (p = 0.001), and preoperative hospital stay >5 days (p = 0.003). The most frequently isolated pathogen was Staphylococcus aureus (53.3%), followed by E. coli (26.7%). Patients with SSIs had a significantly longer mean hospital stay (12.4 days) compared to those without SSIs (6.2 days). Conclusion Surgical site infections remain a significant concern in tertiary care centres, with identifiable and largely preventable risk factors. Effective perioperative management, strict aseptic protocols, and targeted antibiotic prophylaxis can help reduce the incidence of SSIs. Recommendations Implementation of standardized infection control practices, preoperative optimization of comorbidities, reduction of unnecessary hospital stays, and regular microbiological surveillance are essential strategies to mitigate the burden of SSIs in similar healthcare settings.